Analisis perbandingan rencana strategis pada perbankan swasta terkemuka di Indonesia - Royani, Nindy Dwi; Eltari, Miskah Fitriani; Rahim, Sabila Aulia (Maliki Interdisciplinary Journal, 2023)
The community economy is related to the banking industry in a country, both conventional banking and sharia banking. In realizing banking growth, especially in conventional banks, a strategic plan is needed. Where this banking functions in collecting funds and distributing funds to customers and the public. The research was carried out by analyzing the differences in strategic plans at Bank Central Asia, Bank Danamon, and Bank Permata. This research includes research using literature study with a descriptive approach. The source of data collection uses secondary data. The purpose of this research is to find out what the strategic plans of the three banks are and also to find out how to compare the strategic plans between BCA, Bank Danamon and Bank Permata. With a strategic plan, it is hoped that it will be a way to realize the previously promised goals.